The Influence of A Combination of ACT, WDEP Technique, and Butterfly Hug on Reducing Anxiety in Cancer Patients - Cherina Ayu; Riyadi, Agung; Hermansyah, Hermansyah (Jurnal Kesehatan, 2025)
Cancer is a chronic disease that triggers significant psychological anxiety in patients who can negatively affect quality of life and adherence to treatment, making psychological management very important. This study aims to determine the effect of combining Acceptance and Commitment Therapy (ACT), the Wants, Doing, Evaluation, and Planning (WDEP) technique, and the butterfly hug on reducing anxiety among cancer patients. This study employed a quasi-experimental design with a pre-test and post-test and a control group, ensuring comparison between participants who received the intervention and those who did not. 40 patients selected by accidental sampling. The intervention group received a combination therapy of ACT, WDEP, and butterfly hug, while the control group received deep breathing therapy. Anxiety was measured using the STAI-T instrument.  The mean anxiety score before receiving the combined ACT, WDEP, and butterfly hug therapy in the intervention group was 33.0, and after the intervention, it decreased to 27.85. The mean anxiety score before receiving deep breathing therapy in the control group was 31.30, and after the intervention, it decreased to 28.30. The independent samples T-Test showed a p-value≤0.0001. The combination of ACT, WDEP technique, and the butterfly hug proved effective in reducing anxiety levels among cancer patients at the halfway house in Bengkulu City. This combination therapy appears feasible, safe, and potentially effective as a brief psychological intervention for cancer patients. It should be considered as part of supportive care packages in oncology services with ongoing evaluation of its effectiveness and its long-term impact on patients' psychological well-being.